Strength benefit of sawdust/wood ash amendment in cement stabilization of an expansive soil (2019)
The investigation evaluated the strength benefits obtained by amending cement stabilization of an expansive soil by using saw dust ash (SDA), a waste generated in wood milling industries due to burning. The experimental program involved the preparation of cylindrical specimens of size 38 mm x 76mm for evaluating the unconfined compression strength (UCS) of the cement stabilized and amended samples cured for varying periods of 2 hours, 7, 14 and 28 days. Two cement contents of 2% and 6% by weight of soil were adopted to stabilize the soil. The SDA amended cement stabilized samples adopted SDA contents of 5%, 10% and 20% by weight of soil. Strength gain trends for the amended samples were also fitted based on the results of the UCS tests. In order to analyse benefits in pavement design and thickness reduction, the UCS values were used to predict the CBR value of the specimens based on which the reduction in pavement thickness was calculated for different traffic densities. The investigation revealed that 5% SDA amendment of cement stabilization can result in up to 26% increase in early strength and 20% increase in delayed strength. Based on the predicted CBR values, pavement thickness can be reduced up to 8.3%.